The new meaning of educational change - Fullan, Michael (New York : Teachers College Press, 2001)
Over the last few decades there have been attempts at planned educational change. The benefits have not equalled the cost. Fullan distils from these experiences lessons about how to cope with, and influence, educational change.
PART I: UNDERSTANDING EDUCATIONAL CHANGE: A brief history of educational change -- Sources of educational change -- The meaning of educational change -- The causes and processes of initiation -- Causes/processes of implementation and continuation -- Planning, doing, and coping with change -- PART II: EDUCATIONAL CHANGE AT THE LOCAL LEVEL: The teacher -- The principal -- The student --The district administrator -- The consultant -- The parent and the community -- PART III: EDUCATIONAL CHANGE AT THE REGIONAL AND NATIONAL LEVELS: Governments -- Professional preparation of teachers -- Professional development of educators -- The future of educational change.
Includes bibliographical references (p. 273-286) and index.
Keywords: Educational change -- Canada; Educational change -- United States; Education and state -- Canada; Education and state -- United States